Analysis of Phyllosphere Microorganisms and Potential Pathogens of Tobacco Leaves - Xiang, Li-Gang; Wang, Han-Cheng; Wang, Feng; Cai, Liu-Ti; Li, Wen-Hong; Hsiang, Tom; Yu, Zhi-He (Frontiers in Microbiology, 2022)
In the tobacco phyllosphere, some of the microbes may have detrimental effects on plant health, while many may be neutral or even beneficial. Some cannot be cultivated, so culture-independent methods are needed to explore microbial diversity. In this study, both metagenetic analysis and traditional culture-dependent methods were used with asymptomatic healthy leaves and symptomatic diseased leaves of tobacco plants. In the culture-independent analysis, asymptomatic leaves had higher microbial diversity and richness than symptomatic leaves. Both asymptomatic and symptomatic leaves contained several potentially pathogenic bacterial and fungal genera. The putative bacterial pathogens, such as species of Pseudomonas, Pantoea or Ralstonia, and putative fungal pathogens, such as species of Phoma, Cladosporium, Alternaria, Fusarium, Corynespora and Epicoccum, had a higher relative abundance in symptomatic leaves than asymptomatic leaves. FUNGuild analysis indicated that the foliar microbial community also included endophytes, saprotrophs, epiphytes, parasites, and endosymbionts. PICRUSt analysis showed that the dominant functions of the bacterial community in a symptomatic leaf were cellular processes and environmental information processing. In the other five foliar samples, the dominant functions of the bacterial community were genetic information processing, metabolism, and organismal systems. In the traditional culture-dependent method, 47 fungal strains were isolated from 60 symptomatic tobacco leaf fragments bearing leaf spots. Among them, 21 strains of Colletotrichum (29%), Xylariaceae (14%), Corynespora (14%), Pestalotiopsis (10%), Alternaria (10%), Epicoccum (10%), Byssosphaeria (5%), Phoma (5%), and Diaporthe (5%) all fulfilled Koch’s postulates and were found to cause disease on detached tobacco leaves in artificial inoculation tests. Symptoms on detached leaves caused by three strains of Corynespora in artificial inoculation tests were similar to the original disease symptoms in the tobacco field. This study showed that the combined application of culture-dependent and independent methods could give comprehensive insights into microbial composition that each method alone did not reveal.